2006
DOI: 10.1097/01.prs.0000218184.47372.d5
|View full text |Cite
|
Sign up to set email alerts
|

Textured Surface Breast Implants in the Prevention of Capsular Contracture among Breast Augmentation Patients: A Meta-Analysis of Randomized Controlled Trials

Abstract: The results of this meta-analysis demonstrate the superiority of textured over smooth breast implants in decreasing the rate of capsular contracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
174
1
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(188 citation statements)
references
References 36 publications
2
174
1
11
Order By: Relevance
“…The search for prevention and less morbid/invasive treatment for this phenomenon has been the subject of several studies; however, so far, no study has clearly demonstrated their effectiveness [3][4][5][6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The search for prevention and less morbid/invasive treatment for this phenomenon has been the subject of several studies; however, so far, no study has clearly demonstrated their effectiveness [3][4][5][6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…In this type of surgery, the capsular contracture is the main complication 3,4 observed in up to 50% 4,5 of patients in two years following the surgery [3][4][5][6][7] . The fibrous tissue formed around the prosthesis promotes its compression and can cause esthetic involvement (distortion, asymmetry and hardening of the breast) and painful symptoms [4][5][6][7][8][9] , making it sometimes frustrating for both patients and surgeons 5,6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An implant with a textured surface has less contracture than that with a smooth surface [14]. Therefore, textured type implants are thought to be more biocompatible with surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%